A Short Comparison of Two Marine Planktonic Diazotrophic Symbioses Highlights an Un-quantified Disparity - Caputo, Andrea; Stenegren, Marcus; Pernice, Massimo C.; Foster, Rachel A. (Frontiers in Marine Science, 2018)
Some N2-fixing cyanobacteria form symbiosis with diverse protists. In the plankton two groups of diazotrophic symbioses are described: (1) a collective group of diatoms which associate with heterocystous cyanobacteria (Diatom Diazotroph Associations, DDA), and (2) the microalgal prymnesiophyte Braarudosphaera bigelowii and its relatives which associate with the unicellular cyanobacterium Candidatus Atelocyanobacterium thalassa (hereafter as UCYN-A). Both symbiotic systems co-occur, and in both partnerships the symbionts function as a nitrogen (N) source. In this perspective, we provide a brief comparison between the DDAs and the prymnesiophyte- UCYN-A symbioses highlighting similarities and differences in both systems, and present a bias in the attention and current methodology that has led to an under-detection and under-estimation of the DDAs.